جماليات فن الراكو في اعمال الخزاف العراقي سعد العاني (Journal of the College of Basic Education, 2025)
Raku is one of the most prominent firing techniques in contemporary ceramics, due to its aesthetic uniqueness based on spontaneity and chance. Clay, fire, and smoke intertwine to create unexpected forms, revealing philosophical depth and an aesthetic vision open to the unfamiliar. This art has transitioned from its traditional Japanese roots, associated with a life of contemplation and spiritual ritual, to contemporary global experiences that have reshaped it to suit their diverse cultural contexts. In Iraq, potter Saad Al-Ani has emerged as one of the most prominent figures who have exploited the aesthetics of raku, successfully combining the spirit of Eastern technology with the specificity of the local environment. His ceramic works form a dialogue between matter and space, between deliberate coincidence and free organization, presenting organic forms characterized by transformation and constant movement. Through his surface treatments rich in texture and color, Al-Ani has succeeded in giving ceramics a philosophical dimension that transcends their physical function to become a visual discourse reflecting human anxiety and existential questions. Therefore, studying the aesthetics of raku in Saad Al-Ani's works allows